Analisis kebijakan akuntansi koleksi bahan pustaka sebagai barang milik negara di Indonesia - Fajar Islakh Hayadi (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2021)
This study aims to analyze the practices of recording library material collection transactions in the existing system and problems in accounting policies related to library material collection transactions as state property. The case study in this qualitative research uses in-depth interviews, document analysis, and focus group discussions involving the National Library of Indonesia, the Ministry of Finance and the Government Accounting Standards Committee. The results of the study indicate that there are some problems related to recording transactions for collections of library materials, including applicable accounting policies. The study proposes some changes in accounting policies related to library material collection transactions based on Guidance Notes No. 2 Accounting for Libraries based on IPSAS.